Equilibrium in Non-Partitioning Strategies - Robert J. Weber (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Herein we present a single example with three purposes: (1) to show the existence of equilibria in a game which violates the assumptions of currently-available general existence theorems, (2) to illustrate the importance of the "affiliation" assumption in economic games of incomplete information, by showing how even a slight relaxation can lead to the nonexistence of equilibria in monotone strategies, and, most importantly, (3) to exhibit an equilibrium point in strategies which partially reveal information without inducing posterior partitionings of the players' type spaces.
Keywords: 330